ISOLATION AND SCREENING OF LACTIC ACID BACTERIA FROM NATURALLY FERMENTED SOURCES WITH HIGH BIOTECHNOLOGICAL POTENTIAL - LASLO, Éva; GYÖNGYVÉR, Mara; FUNKENHAUZER, Bernadett; DOBRI, Emőke; SALAMON, Rozália Veronika; LÁNYI, Szabolcs; ÁBRAHÁM, Beáta (Studia Universitatis Babeș-Bolyai Chemia, 2015)
A total number of 246 lactic acid bacteria were isolated from naturally fermented traditional foods and feed. These isolates were phenotypically characterized, classified and identified using 16S ribosomal DNA sequencing. 13 different species were detected from cheeses and from fermented plant materials. The isolates belonged to four genera: Lactobacillus genera 87%, Pediococcus 2%, Enterococcus 7%, Leuconostoc 4%. The fermentation capacity of the selected bacterial strains was tested in the presence of three different carbon sources. According to the results the most promising strains were Lactobacillus plantarum subsp. plantarum A5, Lactobacillus plantarum subsp. plantarum C5, Lactobacillus paracasei subsp. Tolerans N16 and Lb. acidipiscis H9. These strains were able to produce high amount of L-lactic acid, contributing to the pH-decrease of the medium. This result indicates that the selected bacterial strains show potential for biotechnological application as starter cultures for silage fermentation.